Punitive Operations of Lithuanian Partisans in Lazdijai County in 1944–1952 (an example of Leipalingis rural district) - Zagreckas, Rimantas (Genocidas ir rezistencija, 2024)
Judging by the whole of military conflicts that had taken place in Central Europe in the 20th century, the 1944–1952 resistance in Lithuania against the Soviet Union occupation distinguishes itself by relatively high indicators of collaborationism fighting. The tactics of mass annihilation of the real or alleged collaborators was especially characteristic of South Lithuania partisan movement. At the time, in Alytus county, which was the largest county in this region, approximately 1450 people were killed by partisans (including clashes with NKVD and MGB squads), while in the other county of this region, Lazdijai, during the same period – about 1800 people.Unlike Central European countries, where during the period of the Second World War, people, who collaborated with the Nazi Germany, more likely were so called right-wing people or fascism supporters, among the post-war Lithuania collaborators with the Soviet Union that had occupied the country more visible were so-called left-wing folks or people supporting the Communist ideology.The statistics of attacks, described in this article, organized by partisans against collaborators in 1944–1952 in the southernmost region of Lithuania – Lazdijai county, and especially in detail in Leipalingis rural district – suggests, that sharpness of the fight against collaborationism differed in Lithuania’s regions. The reason for this was not only different reaction of ordinary inhabitants towards the actions of their fellow citizens (i.e., cooperation with the occupant), but it depended as well on the tactics of the fight against sovietisation of the region chosen differently by resistance leaders. In Lazdijai county, partisan platoons of two large units – Tauras and Dainava military districts – were acting. Statistical indicators speak of obvious differences in the methods of fighting collaborationism in these military districts.Like in West Europe (for example, in France during the Second World War), in Lithuania as well, the most hated social groups were armed platoons, formed from local people by the occupying authorities, and aiming at fighting fellow citizens.
Keywords: Lazdijai region; partisans; collaborators; repressive structures; death cases